Combining a rhesus cytomegalovirus/SIV vaccine with a neutralizing antibody to protect against SIV challenges in rhesus macaques - Coppola, Jessica; Parren, Mara; Bastidas, Raiza; Saye, Karen; Malvin, Jacqueline; Jardine, Joseph G.; Gilbride, Roxanne M.; Ojha, Sohita; Feltham, Shana; Morrow, David; Barber-Axthelm, Aaron; Bochart, Rachele; et al. (Frontiers in Microbiology, 2025)
A vaccine is considered essential for controlling the HIV pandemic and ultimately eradicating AIDS. Neutralizing antibodies and MHC-E-restricted CD8+ T cells have shown the ability to protect against the simian counterpart of HIV, SIV, in rhesus macaques. In this study, we provide preliminary evidence that combining these orthogonal antiviral mechanisms can offer increased protection against SIV. Specifically, the replication arrest observed following vaccination with a rhesus cytomegalovirus (RhCMV/SIV)-based vaccine was enhanced by the presence of a passively administered neutralizing antibody at incompletely protective levels. This report encourages studies involving larger cohorts of macaques and alternative methods for administering neutralizing antibodies.